Detection of New Quorum Sensing N-Acyl Homoserine Lactones From Aeromonas veronii - Gui, Meng; Liu, Lei; Wu, Ruiyun; Hu, Jingrong; Wang, Shun; Li, Pinglan (Frontiers in Microbiology, 2018)
Sturgeon is an important fresh water-culture fish in China. A problem with sturgeon is its high susceptibility to spoilage. Food spoilage is reported to be regulated by quorum sensing (QS). To identify the QS signals acetylated homoserine lactones (AHLs) in sturgeon and test whether QS plays a role in the spoilage of sturgeon, we investigated the specific spoilage organisms (SSOs) in vacuum packaged sturgeon stored at 4°C and the production of AHLs by sturgeon SSOs. 16S rDNA sequencing and spoilage capabilities analysis revealed that Aeromonas veronii LP-11, Citrobacter freundii LPJ-2, and Raoultella ornithinolytica LPC-3 were the SSOs in sturgeon. Among the three SSOs, only A. veronii LP-11 induced the QS biosensors Agrobacterium tumefaciens KYC55 and Chromobacterium violaceum CV026, suggesting that it produced AHLs. Analysis by thin layer chromatography, high-performance liquid chromatography-triple quadrupole tandem mass spectrometry, and high-performance liquid chromatography quadrupole time-of-flight mass spectrometry (HPLC/qTOF-MS) identified that the AHLs produced by A. veronii were C6-SHL, C8-HSL, 3-oxo-C8-HSL, and 3-OH-C8-HSL. Our study revealed that QS system was probably involved in the regulation of sturgeon spoilage and for the first time reported the production of C8-HSL and 3-OH-C8-HSL by genus Aeromonas. As only HPLC/qTOF-MS effectively and accurately identified all the four AHLs produced by A. veronii LP-11, this study also showed that HPLC/qTOF-MS was the most efficient method for rapid analysis of AHLs in complex microbial sample. The study provides new insight into the microbiology of sturgeon spoilage which may be helpful for better sturgeon preservation.